Dampak Social Media Marketing Terhadap Niat Beli dan Loyalitas Pelanggan Scarlett Whitening Official (Jurnal Simki Economic, 2023)
This study discusses the influence of social media marketing using online advertisements, content sharing, credibility towards purchase intention and customer loyalty. The population in this study were users of Scarlett Whitening Official products in the Jakarta and Tangerang areas. The sample in this study amounted to 100 respondents. The analytical tool in this study uses multiple linear regression. The findings in this study indicate that online advertisement, content sharing, and credibility have a significant effect on purchase intention and customer loyalty. Limitations in this study include the number of samples that are still lacking to describe the actual situation, and it is hoped that this research will become informational and learning materials for entrepreneurs to be able to take advantage of technological sophistication as a forum for marketing strategy.